GPR55: A therapeutic target for Parkinson's disease?. (October 2017) - Celorrio, Marta; Rojo-Bustamante, Estefanía; Fernández-Suárez, Diana; Sáez, Elena; Estella-Hermoso de Mendoza, Ander; Müller, Christa E.; Ramírez, María J.; Oyarzábal, Julen; Franco, Rafael; Aymerich, María S.
Abstract: The GPR55 receptor is expressed abundantly in the brain, especially in the striatum, suggesting it might fulfill a role in motor function. Indeed, motor behavior is impaired in mice lacking GPR55, which also display dampened inflammatory responses. Abnormal-cannabidiol (Abn-CBD), a synthetic cannabidiol (CBD) isomer, is a GPR55 agonist that may serve as a therapeutic agent in the treatment of inflammatory diseases. In this study, we explored whether modulating GPR55 could also represent a therapeutic approach for the treatment of Parkinson's disease (PD). The distribution of GPR55 mRNA was first analyzed by in situ hybridization, localizing GPR55 transcripts to neurons in brain nuclei related to movement control, striatum, globus pallidus, subthalamic nucleus, substantia nigra and cortex. Striatal expression of GPR55 was downregulated in parkinsonian conditions. When Abn-CBD and CBD (5 mg/kg) were chronically administered to mice treated over 5 weeks with 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine and probenecid (MPTPp), Abn-CBD but not CBD prevented MPTPp induced motor impairment. Although Abn-CBD protected dopaminergic cell bodies, it failed to prevent degeneration of the terminals or preserve dopamine levels in the striatum. Both compounds induced morphological changes in microglia that were compatible with an anti-inflammatory phenotype that did not correlate with a neuroprotective activity. The symptomatic relief of Abn-CBD was further studied in the haloperidol-induced catalepsy mouse model. Abn-CBD had an anti-cataleptic effect that was reversed by CBD and PSB1216, a newly synthesized GPR55 antagonist, and indeed, two other GPR55 agonists also displayed anti-cataleptic effects (CID1792197 and CID2440433). These results demonstrate for the first time that activation of GPR55 might be beneficial in combating PD. Highlights: GPR55 is a therapeutic target for Parkinson's disease. GPR55 is highly expressed in basal ganglia. Abn-CBD improves motor behavior in parkinsonian mice models. Abn-CBD protects dopamine neuron cell bodies but not terminals. GPR55 mediates the symptomatic relief exerted by Abn-CBD.